Zircon Lu-Hf isotopic compositions of the Paleoproterozoic meta-mafic and felsic rock assemblages in the Daqingshan complex: constraints on crustal evolution of the Khondalite Belt, north China Craton - Wang, Han; Chen, Jinfeng; Zhou, Ningchao; Zhang, Xiaoyang; Kong, Weijiang; Ma, Ben (Frontiers in Earth Science, 2025)
Nowadays, the Khondalite Belt is considered to be a typical continent-continent collisional belt, formed by the collision of the Yinshan Block and the Ordos Block at 1.95–1.85 Ga. However, the pre-collisional tectonic setting and crustal evolutionary history of the Khondalite Belt are poorly constrained. In order to better understand the crustal evolution of the Khondalite Belt, zircon Lu-Hf isotopes and trace elements have been studied based on the published zircon U-Pb age data of the meta-mafic and felsic rock assemblages from the Daqingshan Complex. The zircon U-Pb dating results indicate that the meta-mafic and felsic rock assemblages yield crystallization ages ranging from 2.47 to 2.39 Ga, with metamorphic ages between 1.91 and 1.83 Ga. The zircon Hf isotopic data from meta-mafic rocks have εHf(t) values of −0.3 to +9.7. The depleted-mantle two-stage zircon Hf model ages range from 2,951 to 2,324 Ma and are mainly concentrated at 2.8 to 2.6 Ga, indicating that the primary magma originated from partial melting of the depleted lithospheric mantle. The zircon Hf isotopic data from felsic rocks have εHf(t) values of +2.4 to +9.1, indicating that these samples were derived from partial melting of juvenile crustal materials. In addition, the trace element characteristics of the zircons indicate that they were formed in the continental arc-related/orogenic tectonic setting. Combined with previous studies, it is proposed that the meta-mafic and felsic rock assemblages within the Daqingshan Complex represent the magmatic product formed by the early Paleoproterozoic continental magmatic arcs along the southern margin of Yinshan Block. In summary, it can be inferred that Khondalite Belt experienced long-lived arc-continental accretion along the southern margin of the Yinshan Block during the late Neoarchean to Paleoproterozoic, subsequently followed by collision between Yinshan and Ordos Blocks and merged into an integrated Western Block at ca. 1.95–1.85 Ga.